Exploring of InDel in bovine PSAP gene and their association with growth traits in different development stages. Issue 1 (1st February 2022) - Wang, Shuhui; Zhao, Haidong; Wu, Mingli; Yi, Xiaohua; Chen, Pingbo; Liu, Shirong; Pan, Yun; Li, Qi; Tang, Xiaoqin; Sun, Xiuzhu
Abstract: PSAP (prosaposin) is widely expressed in different organs, and plays an important role in fat deposit. Insertion/Deletion (InDel) is a relatively simple and effective DNA marker. However, the association of molecular marker at different stages of animal development has not received enough attention, especially fat deposition related traits. Therefore, eight cattle breeds were used to explore novel InDels variants within bovine PSAP gene, and to evaluate their effects on growth traits in different development stages. Herein, two novel InDels (P5:NC037355.1g.27974439-27974440 ins AGTGTGGTTAATGTCAAC and P8:NC037355.1g.27980734-27980752 del GTCAAAAAATCAGGGGAAAC) within the bovine PSAP gene were found, and their association with growth traits in different development stages were analyzed. Interestingly, the dominant genotype was different in different development stages both in NY cattle and JX cattle for daily gain and body weight. PSAP Gene expression patterns were analyzed in this study, high expression in the middle stage of adipocytes differentiation suggests that it plays a certain role in fat development. It reveals that InDels could affect phenotype in different development stages, which depend on the expression pattern of the host gene and their function in different tissues. These findings could provide a new way for molecular marker studies in bovine breeding and genetics.